Altered cerebellar connectivity in autism and cerebellar-mediated rescue of autism-related behaviors in mice. (December 2017) - Stoodley, Catherine; D'Mello, Anila; Ellegood, Jacob; Jakkamsetti, Vikram; Liu, Pei; Nebel, Mary; Gibson, Jennifer; Kelly, Elyza; Meng, Fantao; Cano, Christopher; Pascual, Juan; Mostofsky, Stewart; et al.
Abstract Cerebellar abnormalities, particularly in Right Crus I (RCrusI), are consistently reported in autism spectrum disorders (ASD). Although RCrusI is functionally connected with ASD-implicated circuits, the contribution of RCrusI dysfunction to ASD remains unclear. Here neuromodulation of RCrusI in neurotypical humans resulted in altered functional connectivity with the inferior parietal lobule, and children with ASD showed atypical functional connectivity in this circuit. Atypical RCrusI–inferior parietal lobule structural connectivity was also evident in the Purkinje neuron (PN)TscI ASD mouse model. Additionally, chemogenetically mediated inhibition of RCrusI PN activity in mice was sufficient to generate ASD-related social, repetitive, and restricted behaviors, while stimulation of RCrusI PNs rescued social impairment in the PNTscI ASD mouse model. Together, these studies reveal important roles for RCrusI in ASD-related behaviors. Further, the rescue of social behaviors in an ASD mouse model suggests that investigation of the therapeutic potential of cerebellar neuromodulation in ASD may be warranted. Cerebellar right Crus I (RCrusI) has been implicated in autism spectrum disorder (ASD). RCrusI modulation altered RCrusI–inferior parietal lobule connectivity, and this connectivity was atypical in children with ASD and in aTscI mouse model of ASD. Inhibition of RCrusI in mice led to autism-related behaviors, and RCrusI activation rescued social impairments inTscI mice.